Internalization Of Islamic Values Through Aqidah Akhlak Learning: A Qualitative Field Research - Rauf, Ahmad; Karwono; Aguswan Khotibul Umam (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2026)
This study examines the concepts, processes, and strategies of internalizing Islamic values through Aqidah Akhlak learning to shape students' character amid globalization and increasing social challenges. This research is based on the assumption that Aqidah Akhlak learning does not merely emphasize cognitive aspects but also facilitates the transformation of aqidah, ibadah, and akhlak values into actual behavior. Using a qualitative field research approach at MAN 1 Lampung Timur, this study analyzes data collected through semi-structured interviews with teachers and students, classroom observations, and documentation. Using interactive qualitative analysis, this study identifies that the internalization of Islamic values occurs through three interconnected phases: cognitive understanding, affective internalization, and behavioral practice. These three phases are influenced by three main factors, namely instructional strategies, teacher exemplarity, and the religious culture of the school environment. Teachers play a central role as mu'allim (instructors), murabbi (moral guides), and qudwah hasanah (role models) in facilitating the entire internalization process. The main contribution of this study is the presentation of a conceptual framework that systematically integrates the stages of value internalization with their supporting factors. This framework provides a more comprehensive understanding of how Aqidah Akhlak learning can shape students' character, particularly in fostering akhlak al-karimah and strengthening resilience against the negative impacts of globalization